Analysis of Company Policies and Strategies Based on Identification of The Contribution Technology Needs in MSMEs Leather Processing Industry - Helmi, Adlina Safitri; Ramadhani, Indah Kurnia (Universitas Al Azhar Indonesia, 2025)
Technology is crucial to the success of any company, especially for Micro, Small and Medium Enterprises (MSME). MSMEs XYZ is a small and medium industry in Bandung that processes leather into bags. As a result, it is vital to boost technology by conducting a technology management analysis on these SMEs in order to maintain quality products and compete with the competition. This research aims to use the technology assessment analysis based on Technometrics models as a foundation for evaluating strengths and weaknesses linked to products and processes in MSMEs XYZ in order to get alternative strategies and policies. The measured technology components include technoware (production equipment), humanware (human resource capabilities), infoware (information tools), and orgaware are the measured technological components (organizational tools). The component contribution values for technoware (0,223), humanware (0,688), infoware (0,156), and orgaware (0,311). The Technologies Contribution value received (0,279) is a type of traditional technology with a low classification level. Recommendation for this research is acquisition within procurement of manufacturing machinery and equipment. In order to preserve company sustainability in terms of technology, MSMEs XYZ to raise investment, update products and manufacturing methods, and expand human resources.Keywords: MSME, Production, Technometrics Model.